A crusade against the curve? Physical education for disabled pupils in France after World War II (1945–1958). (3rd July 2020) - Tajri, Yacine; Saint-Martin, Jean; Froissart, Tony
ABSTRACT: This article explores a specific physical rehabilitation in French schooling after the Second World War. To this end, it analyses how, in concepts and as the result of data-derived information, pupils considered as "weak" physically speaking were taken care of by the school and especially how the actors of the physical education (PE) system got together to make a cultural offer in line with what were considered to be their needs and aptitudes. Indeed, after a meticulous summary of some of their body measurements and physical displays, the pupils are thus classified into groups where they were taught a kind of PE, considered as the most appropriate to their needs. The paper also focuses on how, during a particular social and political context, the school developed corrective gymnastics as an original pedagogy for disabled pupils of the third group who were to be taught in a new location, the physical rehabilitation centres.